ASPEK BIOLOGI DAN MANFAAT EKONOMI IKAN YANG TERTANGKAP DI SUNGAI SEBANGAU KOTA PALANGKARAYA KALIMANTAN TENGAH - Infa Minggawati; Mardani Mardani; Ricke Marianty (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2020)
This study aims to determine the biological aspects of snakehead fish, kerandang fish, fish and kapar fish caught in the Sebagau river and the economic benefits for fishermen. Analysis of the relationship between length and weight of fish showed a close relationship between fish length and weight with a positive allometric growth pattern. The results of the analysis of fish stomach contents to determine fish food habits showed that the dominant food types were fish fry for Kehung fish 87%, Kerandang 95% and Gabus 99%. Meanwhile, for kapar fish, food dominates in the form of plants 72%. The fishing ground along the Sebangau watershed is in a tributary that is directly connected to the Sebangau river. Economically, the fish catch in the Sebangau river by fishermen is sufficient to fulfill family life.